(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In tracing the evolution ofeducation in India one needs must begin with the system of general educationand its beginnings of what today we loosely term “education” as it wasunderstood and practiced in ancient India. The earliest recorded system ofeducation per se is found in the Rig Veda, which broadly deals with thephilosophy of life and the practices in learning (generally speaking, the wordVeda means” to know.”) It is called the Vedic Era in the history of educationin India and is thought to be almost 5000 years old.